Post-visit factors influencing multifaceted destination image formation - Hashim, Noor Hazarina (2015)
Destination image, significant for destination positioning and destination selection, has been of great interest to researchers since the 1970s. Despite almost four decades of study, the research is still inconclusive on the destination image construct and on factors influencing destination image formation. This paper incorporates multisensory image alongside cognitive, affective and conative image as part of the destination image construct, and emphasises the post-visit factors that influence destination image formation. This framework will be tested as the next stage of the study.